Pengaruh Manajemen Kinerja, Pelatihan dan Budaya Organisasi terhadap Kinerja Karyawan BSI dengan Variabel Reward sebagai Moderasi Perspektif Maqāşid Al-Sharīah - Luthfiana, Nuriya (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of performance management, training andorganizational culture on the performance of BSI employees with the reward variable as a moderating maqāşid al-sharīah perspective. This research is a quantitative research using primary data, namely data taken directly from the respondents' answers. The number of samples in this study were 70 respondents. The analytical method used was technical data analysis in this study using multiple linear regression analysis, hypothesis testing and using the moderated regression analysis (MRA) test. Data management in this study uses the IBM SPSS 25 software program.The results of this study indicate that performance management and training have no effect on the performance of BSI employees. And organizational culture has an influence on employee performance from the perspective of maqāşid al-sharīah. The results of this study also show that performance management, training and organizational culture together have an influence on employee performance from the maqāşid al-sharīah perspective. Then the reward variable can moderate the influence of organizational culture on employee performance while performance management and training are not moderated by rewards. Keywords: Performance Management, Training, Organizational Culture, Employee Performance, Reward.